Future of an 'asymptomatic'' T-cell epitope-based therapeutic herpes simplex vaccine. (April 2012) - Dervillez, Xavier; Gottimukkala, Chetan; Kabbara, Khaled W; Nguyen, Chelsea; Badakhshan, Tina; Kim, Sarah M; Nesburn, Anthony B; Wechsler, Steven L; BenMohamed, Lbachir
Considering the limited success of the recent herpes clinical vaccine trial, new vaccine strategies are needed. Infections with HSV-1 and HSV-2 in the majority of men and women are usually asymptomatic and result in lifelong viral latency in neurons of sensory ganglia. However, in a minority of men and women, spontaneous HSV reactivation can cause recurrent disease (i.e., symptomatic individuals). Our recent findings show that T cells from symptomatic and asymptomatic men and women (i.e., those with and without recurrences, respectively) recognize different herpes epitopes. This finding breaks new ground and opens new doors to assess a new vaccine strategy: mucosal immunization with HSV-1 and HSV-2 epitopes that induce strong in vitro CD4 and CD8 T-cell responses from peripheral blood mononuclear cells derived from asymptomatic men and women (designated here as 'asymptomatic'' protective epitopes) could boost local and systemic 'natural'' protective immunity, induced by natural infection. Here we highlight the rationale and the future of our emerging asymptomatic T-cell epitope-based mucosal vaccine strategy to decrease recurrent herpetic disease.